Association between Self-esteem and Body Image with Marital Satisfaction in Iranian Women with Vaginismus: A Cross-Sectional Study - Ziaei, Saeideh; Velayati, Atefeh; Jahanian Sadatmahalleh, Shahideh; Fathnezhad-Kazemi, Azita (Advances in Nursing & Midwifery, 2024)
Introduction: Vaginismus is a common sexual dysfunction in women that, by negatively affecting mental health, can impact the quality of marital relationships or marital satisfaction. This study aimed to determine the relationship between self-esteem, body image, and marital satisfaction in women with vaginismus. Methods: This cross-sectional study was conducted on 236 women with vaginismus who were selected with convenience sampling method in sexual health clinics in Tehran, Iran, in 2018. Data were collected through questionnaires including socio-demographic characteristics, ENRICH marital satisfaction, Rosenberg self-esteem, and body image. Pearson correlation analysis was used to determine the relationship between self-esteem, body image, and marital satisfaction as bivariate analysis, and a general linear model with adjustment for socio-demographic characteristics was used for multivariate analysis using SPSS software, Version 24. Results: The average age of women was 31.48(5.48) and more than 80% had a university education. And 75% of women had a history of vaginismus for more than one year. The mean (SD) scores for marital satisfaction, self-esteem, and body image were 31.55(7.12), 17.42(5.46), and 41.45(13.13), respectively. According to Pearson correlation results, there was a significant positive correlation between self-esteem and marital satisfaction (r= 0.43, p-value <0.001), and a significant negative correlation between body image and marital satisfaction (r=-0.31, p-value < 0.001). The results of the linear model with adjustment for socio-demographic variables indicated that an increase in self-esteem scores (B=0.42; 95% CI: 0.25 to 0.59; P<0.001) led to an increase in marital satisfaction while worsening body image (B= -0.08; 95%CI: -0.15 to -0.20) was associated with a decrease in marital satisfaction. Conclusions: Increased self-esteem and reduced body image concerns are associated with higher marital satisfaction among women with vaginismus. Therefore, Identifying these people, factors affecting the disease, management and control of the factors involved, and counseling interventions to enhance self-esteem and improve body image are recommended for this group of women.